ONLINE LEARNING FOR IMAGE PROCESSING IN NETWORKED SETTING - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
In the past decade development of machine learning algorithm for network settings has witnessed little advancements owing to slow development of technologies for improving bandwidth and latency.Â  In this study we present a novel online learning algorithm for network based computational operations in image processing setting